A Metatheoretical Evaluation of Chaordic Systems Thinking. (29th May 2013) - Edwards, Mark G.
<x xml:space="preserve">Abstract</x> This paper presents a metatheoretical evaluation of chaordic systems thinking (ChST) as it applies to organizational transformation. The diversity of approaches to transformation means that it is rich territory for metatheoretical research. ChST can be regarded as a metatheoretical attempt to integrate conceptual lenses so that a richer conceptualisation of transformation can be developed. ChST aims to be an integrative and innovative theoretical contribution to understanding change. How might these claims be evaluated? A metatheoretical method called metatriangulation is applied here to evaluate the ChST framework. A review and analysis of 20 ChST texts was performed and found that the approach shares several lenses with other theories of organizational transformation, but it also omits some important lenses and only partially described others. Recommendations for the further development of ChST are presented. Although important for developing novel insights, metatheoretical research is rarely performed systematically. This paper presents an original approach to building and evaluating overarching frameworks for organizational transformation. Copyright © 2013 John Wiley & Sons, Ltd.